A Theory of Board Control and Size - Harris, Milton; Raviv, Artur (Review of Financial Studies, 2008)
[This article presents a model of optimal control of corporate boards of directors. We determine when one would expect inside versus outside directors to control the board, when the controlling party will delegate decisionmaking to the other party, the extent of communication between the parties, and the number of outside directors. We show that shareholders can sometimes be better off with an insidercontrolled board. We derive endogenous relationships among profits, board control, and the number of outside directors that call into question the usual interpretation of some documented empirical regularities.]